The prediction of X2B6 monolayers with ultrahigh carrier mobility - Du, Xiuzhi; Huang, Zhaoming (Frontiers in Physics, 2025)
Two-dimensional (2D) materials present novel electronic and catalytic performances, showing a promising application as nano-device. In this investigation, a family of 2D material, X2B6 (X = K, Na and Rb), is predicted with puckered crystal structure by elemental mutation method. The dynamic and thermal stability of the X2B6 monolayer is addressed. The anisotropic mechanical properties of the X2B6 monolayer is obtained by the Young’s modulus (296–406 N/m) and the Poisson’s ratio (0.36–0.35). Interestingly, the K2B6 and Rb2B6 monolayers demonstrate a metallic band structure, while the Na2B6 monolayer is a semiconductor with an ultra-narrow bandgap only about 0.42 eV. Then, the ultra-high electron mobility in the Na2B6 monolayer is calculated as about 9942 cm2.V−1.s−1, and the excellent optical performance of the Na2B6 monolayer is also addressed. More importantly, the advantageous catalytic activity in hydrogen evolution reduction (HER) and oxygen evolution reactions (OER) is explored in these X2B6 monolayers. Our work suggests a theoretical guidance to use the X2B6 monolayer as a high-speed electronic devices and highly efficient catalyst.